The Impact of the Covid-19 Pandemic on the Environment:: Environmental Diplomacy on Handling Covid-19 Medical Waste in Indonesia - Firmalasari, Benita Kristi; Rasyidah, Resa (WIMAYA, 2020)
The Covid-19 pandemic has had a significant impact on the environment. The enormous need for personal protective equipment (PPE) masks (both medical and non-medical masks), protective clothing, face shields, gloves to hand sanitizers and disinfectants has resulted in the accumulation of medical waste in some regions in Indonesia. This paper aims to describe the environmental diplomacy and international cooperation efforts undertaken by the Indonesian government to address these problems. The author finds that Indonesia's environmental diplomacy was carried out before the pandemic occurred, but not much has focused on medical waste management. International cooperation to overcome the problem of medical waste accumulation has been carried out with some countries such as Japan, ASEAN and also WHO. Of course, considering that this pandemic is still ongoing, it is hoped that this paper can be the start of research and can be used as a stepping stone for further research.